Early Stroke and Mortality After Percutaneous Left Atrial Appendage Occlusion in Patients With Atrial Fibrillation. Issue 4 (3rd March 2023) - Kogan, Edward V.; Sciria, Christopher T.; Liu, Christopher F.; Wong, S. Chiu; Bergman, Geoffrey; Ip, James E.; Thomas, George; Markowitz, Steven M.; Lerman, Bruce B.; Kim, Luke K.; Cheung, Jim W.
Abstract : Background: Percutaneous endocardial left atrial appendage occlusion (LAAO) is an alternative therapy for stroke prevention in patients with atrial fibrillation who are poor candidates for oral anticoagulants. Oral anticoagulation is generally discontinued 45 days following successful LAAO. Real-world data on early stroke and mortality following LAAO are lacking. Methods: Using International Classification of Diseases, Tenth Revision, Clinical-Modification codes, we performed a retrospective observational registry analysis to examine the rates and predictors of stroke, mortality, and procedural complications during index hospitalization and 90-day readmission among 42 114 admissions in the Nationwide Readmissions Database for LAAO between 2016 and 2019. Early stroke and mortality were defined as events occurring during index admission or 90-day readmission. Data on timing of early strokes post-LAAO were collected. Multivariable logistic regression modeling was used to ascertain predictors of early stroke and major adverse events. Results: LAAO was associated with low rates of early stroke (0.63%), early mortality (0.53%), and procedural complications (2.59%). Among patients who had readmissions with strokes after LAAO, the median time from implant to readmission was 35 days (interquartile range, 9–57 days); 67% of readmissions with strokes occurred <45 days postimplant. Between 2016 and 2019, the rates of early stroke after LAAO significantly decreased (0.64% versus 0.46% P -for-trend <0.001), while early mortality and major adverse event rates were unchanged. Peripheral vascular disease and a history of prior stroke were independently associated with early stroke after LAAO. Early post-LAAO stroke rates were similar between low, medium, and high LAAO volume tertile centers. Conclusions: In this contemporary real-world analysis, the early stroke rate after LAAO was low, with the majority occurring within 45 days of device implantation. Despite an increase in LAAO procedures between 2016 and 2019, there with a significant decline in early strokes after LAAO during that period.